EQUILIBRIUM OF LEAD (II) BIOSORPTION AND CHARACTERIZATION THROUGH FT-IR AND SEM-EDAX ON Ascophyllum nodosum SEAWEED - Ale Borja, Neptalí (2015)
Lead (II) biosorption on Ascophyllum nodosum seaweed at 20°C and initial pH 4-5 wasstudied, by using models of Langmuir and Freundlich isotherms. In order to establishseaweed, CaCl2 was used. The granulometry used in the biosorbent was 0-75 μm. In Fourier transform infrared spectroscopy, FT-IR, a shift in the signal of carbonyl group of crosslinkedsample before metal biosorption and after (1600.92 cm-1 to 1573.91 cm-1) and 1400 cm-1 (thatwas from 1415.75 cm-1 to 1409.96 cm-1) was observed, suggesting a chelating (bidentate)character of the metal biosorption onto carboxylic groups that belongs to the units of alginatemonomeric. The bands at 3305.99 cm-1 allowed the recognition of hydroxyl groups in thebiosorbent. The scanning electronic microscopy, SEM, verified heterogeneity of biosorbentparticles. In the energy-dispersive X-ray spectroscopy, EDAX, a very strong signal in thecarbon and another less strong for the oxygen characteristic of the biopolymer were observed.The signal of calcium could be recognized in EDAX spectra of the sample after pre-treated.The two peaks that correspond to lead element were observed in the sample after biosorptionprocess. Experimental data of biosorption equilibrium had greater correlation coefficient toLangmuir isotherm model, reaching the maximum sorption capacity, qmax, of 228 mg/g. Lead(II) residual concentration, Ceq, in the solutions after getting equilibrium, was determinedafter 72h starting the process by atomic absorption spectroscopy. For data processing andstatistic treatment, Origin 6.0 informatics program was used.